2016
DOI: 10.1097/md.0000000000002709
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Whole-Body Vibration Training Without Visual Feedback on Balance and Lower-Extremity Muscle Strength of the Elderly

Abstract: The purpose of this study was to investigate the influence of whole-body vibration (WBV) training without visual feedback on balance and lower-extremity muscle strength in the elderly.Elderly subjects who did not exercise regularly participated in this study. Subjects were randomly divided into a WBV with eyes open group, a visual feedback-deprived plus WBV (VFDWBV) group, and a control group (0 Hz, eyes open). WBV training was provided over a 3-month period, 3 times per week for 5 min each session. Balance pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
(43 reference statements)
1
14
0
1
Order By: Relevance
“…WBV exercises have been widely used for the benefits of pain reduction, muscle strength increase, proprioception, balance and posture control, and functional performance improvement in postmenopausal women and sedentary and older individuals [17,19,34,35,36]. A recent study investigating the effects of WBV in addition to home exercise in female patients with patellofemoral pain also reported decreased pain and improved knee extensor endurance, which may alter lower extremity kinematics and reduce patellofemoral stress [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBV exercises have been widely used for the benefits of pain reduction, muscle strength increase, proprioception, balance and posture control, and functional performance improvement in postmenopausal women and sedentary and older individuals [17,19,34,35,36]. A recent study investigating the effects of WBV in addition to home exercise in female patients with patellofemoral pain also reported decreased pain and improved knee extensor endurance, which may alter lower extremity kinematics and reduce patellofemoral stress [37].…”
Section: Discussionmentioning
confidence: 99%
“…Low frequency, low amplitude mechanical stimuli using a vibrating platform could stimulate the muscle spindles via tonic vibration reflex and send nerve impulses to increase muscle contraction [15]. Whole body vibration (WBV) exercise has been suggested as an alternative treatment to reduce pain and improve muscle strength, balance, and flexibility in sedentary and older people [16,17,18,19]. In knee OA, the effects of WBV in improving knee pain, quadricep strength, and functional performance remain inconclusive [20,21], however, recent randomized controlled trials provided evidence of additive effects of WBV in increasing knee extensor strength and improving physical functions [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have examined the effects of WBV in older adults, only four other studies have assessed if WBV benefits can be retained over time (13)(14)(15)(16). These studies assessed performance after a washout period of three weeks, three months, and six months, respectively, and found that participants were not able to sustain WBV training benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Uma nova forma, considerada promissora, de estimulação somatossensorial é a terapia vibratória. A vibração é definida como um movimento oscilatório dependente da frequência, da amplitude, duração e do tipo de vibração, podendo ser potente estímulo para respostas neuromusculares [4,15].…”
Section: Introductionunclassified